1998
DOI: 10.1002/jlb.63.6.683
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytes of the intestinal muscularis: their phenotype and isolation

Abstract: The basal presence of immunologically potent cells within the intestinal muscularis externa and their functional significance is unclear. Our aim was to investigate the basal distribution of various leukocyte populations within the rat jejunal muscularis. In addition, we sought to immunohistochemically phenotype the muscularis macrophage in jejunal whole-mounts, isolate these cells in primary culture, and investigate their ontogenesis. Macrophages form a regularly distributed network that expresses major histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 0 publications
2
95
0
3
Order By: Relevance
“…Our group has previously demonstrated that prostanoids produced by COX-2 and NO produced by iNOS have potent inhibitory effects on intestinal smooth muscle contractility and that inhibition of the COX-2 enzyme or the selective knockout of the leukocyte-derived iNOS gene averts the development of postoperative ileus (27,49). Additionally, CO treatment before intestinal manipulation decreased iNOS gene expression and NO production in mice (37).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously demonstrated that prostanoids produced by COX-2 and NO produced by iNOS have potent inhibitory effects on intestinal smooth muscle contractility and that inhibition of the COX-2 enzyme or the selective knockout of the leukocyte-derived iNOS gene averts the development of postoperative ileus (27,49). Additionally, CO treatment before intestinal manipulation decreased iNOS gene expression and NO production in mice (37).…”
Section: Discussionmentioning
confidence: 99%
“…Histochemical and immunohistochemical analysis was performed on whole mounts of the intestinal muscularis as described previously (N = 5-7) (20,23). Myeloperoxidase (MPO)-positive cells were detected using HankerYates reagent (Polysciences Europe GmbH, Eppelheim, Germany).…”
Section: Histochemistry and Immunohistochemistrymentioning
confidence: 99%
“…The functional, molecular, and cellular mechanisms determining POI are to be found within the intestinal muscularis. The changes within intestinal mucosa do not influence the cellular and molecular mechanisms of POI (35,37,39,41,42,67,80,82). Previously, we could show a recruitment of CD11bϩCD103ϩ dendritic cells into the intestinal muscularis, but not into the colonic muscularis after IM, which induced a T H 1 response by producing IL-12 at the manipulated site.…”
Section: Discussionmentioning
confidence: 74%
“…Specimens for histochemical analysis were prepared 24 h after surgical procedure and performed on whole mounts of the distal jejunum and the colon (n ϭ 5-7 each group) as described before (41). Freshly prepared whole mounts were stained with Hanker-Yates reagent as described previously (88).…”
Section: Myeloperoxidase Stainingmentioning
confidence: 99%
See 1 more Smart Citation